2015
DOI: 10.1158/1538-7445.sabcs14-p5-19-27
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-19-27: IMMU-132, a new antibody-drug conjugate (ADC) against Trop-2, as a novel therapeutic for patients with relapsed/refractory, metastatic, triple-negative breast cancer (TNBC): Results from Phase I/II clinical trial (NCT01631552)

Abstract: Background: TNBC, comprising 15-20% of all invasive breast cancers, represents an aggressive phenotype with high risk of recurrence and mortality. Trop-2 is a cell-surface glycoprotein expressed on many human carcinomas, including TNBC. High Trop-2 expression is associated with more aggressive disease and poor prognosis in several cancers, including breast cancer. We report interim results from a Phase I/II trial evaluating a novel ADC, IMMU-132 (isactuzumab govitecan), comprising a humanized anti-Trop-2 antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…ELISA monitoring of IgG in the serum found that it clears more slowly, staying in the circulation for a longer period. Similar results are being found in patient samples (34)(35)(36)(37), where (i) the IgG component clears more slowly than the conjugate, (ii) >95% of the total SN-38 in the serum is bound to the IgG, (iii) the amount of free SN-38G in the serum is only a fraction of the free SN-38, and (iv) there is no evidence of glucuronidation of SN-38 bound to IgG. Analysis of serum samples taken from patients given 8 to 10 mg/kg of IMMU-132 on days 1 and 8 of 21-day cycles has found free SN-38 concentrations at levels of about 100 ng/mL 30 minutes after the end of a 2-to 3 h-infusion, whereas the total SN-38 levels average about 4,000 ng/mL (34).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…ELISA monitoring of IgG in the serum found that it clears more slowly, staying in the circulation for a longer period. Similar results are being found in patient samples (34)(35)(36)(37), where (i) the IgG component clears more slowly than the conjugate, (ii) >95% of the total SN-38 in the serum is bound to the IgG, (iii) the amount of free SN-38G in the serum is only a fraction of the free SN-38, and (iv) there is no evidence of glucuronidation of SN-38 bound to IgG. Analysis of serum samples taken from patients given 8 to 10 mg/kg of IMMU-132 on days 1 and 8 of 21-day cycles has found free SN-38 concentrations at levels of about 100 ng/mL 30 minutes after the end of a 2-to 3 h-infusion, whereas the total SN-38 levels average about 4,000 ng/mL (34).…”
Section: Discussionsupporting
confidence: 88%
“…IMMU-132 was found to deliver much higher levels of SN-38 to tumors than irinotecan and, importantly, all of the SN-38 delivered to the tumor by IMMU-132 is released in its most potent form. In relationship to gastrointestinal toxicity, the much lower amounts of SN-38G in the serum and significantly lower amounts of SN-38/SN38G in the intestine with IMMU-132 are expected to reduce the risk for severe diarrhea in patients, which is confirmed in clinical studies (34)(35)(36)(37)(38). Thus, IMMU-132 is an ADC that appears to have unique properties that combine to make an effective therapeutic agent in the solid cancers tested.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, responses in patients with TNBC and SCLC are of particular interest, given the need for targeted therapies in these indications. Indeed, additional partial responses in patients with TNBC and SCLC observed in the ongoing expansion phase of this trial (16, 17) have suggested further emphasis on these cancers, but encouraging responses in NSCLC, EAC, UBC, and CRC are also being followed. Indeed, in a recent update of the ongoing phase II trial of sacituzumab govitecan, an overall response rate (PR) of 30%, with 40% clinical benefit rate (PR + SD ≥6 months) has been observed in 23 patients with metastatic TNBC (16).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, additional partial responses in patients with TNBC and SCLC observed in the ongoing expansion phase of this trial (16, 17) have suggested further emphasis on these cancers, but encouraging responses in NSCLC, EAC, UBC, and CRC are also being followed. Indeed, in a recent update of the ongoing phase II trial of sacituzumab govitecan, an overall response rate (PR) of 30%, with 40% clinical benefit rate (PR + SD ≥6 months) has been observed in 23 patients with metastatic TNBC (16). Long-term survival (15-20+ months) was observed for almost 25% (6/25) of the patients studied, and included 2 with PRs and 4 with SD, including patients with TNBC (N=2), CRC (N=3), and HRPC (N=1).…”
Section: Discussionmentioning
confidence: 98%